DETERMINAN NILAI PERUSAHAAN PADA PERUSAHAAN NON-KEUANGAN YANG TERCATAT DI BURSA EFEK INDONESIA - ZAHRA AFIFAH; MEINIE SUSANTY (Jurnal Bisnis dan Akuntansi, 2019)
The purpose of this study is to determine and examine financial aspects (measured by financial ratio such as financial leverage, profitability, investment opportunity, dividend policy, liquidity, capital structure, and earnings per share), characteristic aspect (measured by firm size), and corporate governance (measured by managerial ownership, independent board of commissioners, and audit committee) in affecting firm value in nonfinancial companies listed in Indonesia Stock Exchange. This research used 59 listed non-financial companies in Indonesia Stock Exchange, selected using purposive sampling method in period 2013 to 2016. The analysis was performed using multiple linear regressions analysis method to determine the model of research. The research results show that profitability, dividend policy, earnings per share, and independent board of commissioners had influence towards firm value.